Air pollution modelling to predict maximum ground level concentration for dust from a palm oil mill stack - Anthonysamy, Regina A.; Ismail, Mohd Halim Shah (Chemical Engineering Department, College of Engineering, Syiah Kuala University, 2010)
The study is to model emission from a stack to estimate ground level concentration from a palm oil mill. The case study is a mill located in Kuala Langat, Selangor. Emission source is from boilers stacks. The exercise determines the estimate the ground level concentrations for dust to the surrounding areas through the utilization of modelling software. The surround area is relatively flat, an industrial area surrounded by factories and with palm oil plantations in the outskirts. The model utilized in the study was to gauge the worst-case scenario. Ambient air concentrations were garnered calculate the increase to localized conditions.